Comparison of Effectiveness of Management of the Conventional Pap Smear: Wet Slides and Dry Slides - Booncharoen, Prachumporn (Journal of Health Science of Thailand, 2018)
The retrospective study of effectiveness was to compare results and management of Pap smear slides in the bottles of fixative 95% ethyl alcohol to the conventional one with dry slides at all of health service units in Surin province. The Pap smear slides were divided into three groups, conventional Pap smear dry slides (October 2002 to September 2003) and Pap smear slides in the bottles of fixative with paper clips on the frosted end of the slides (October 2003 to September 2006) and Pap smear slides in the bottles of fixative with paper clips and colorless plastic bands on the frosted end of the slides (October 2006 to September 2008). Comparisons of the results were made between the three groups and presented in percentage, time used in each steps and advantages. The study revealed that the new management of Pap smear slides in the bottles of fixative had more advantages than the conventional Pap smear dry slides. The Pap smears slides in the bottles of fixative reduced the unsatisfactory results from 2.32 percent to 0.50 percent in the third group(about 5-6 times) and wiped out the obscure results and fungus contamination. Whereas the steps, time and cost were reduced, with impressive quality improvements.